SME Marketing Performance: A Mixed-Method Study on Resilient Compositional Capability - Sugianto Sugianto; Ramadania Ramadania; Wenny Pebrianti (Asia Marketing Journal)
This study examines how Small and Medium Enterprises (SMEs) in developing markets achieve marketing performance through resilient compositional capability despite resource constraints. Using data from 435 SMEs in West Borneo, Indonesia, and employing a mixed-method approach, we find that marketing innovation, government support, and organizational ambidexterity positively influence resilient compositional capability. Our results show that while government support and organizational ambidexterity directly impact marketing performance, marketing innovation's effect is mediated by resilient compositional capability. Furthermore, we find that resilient compositional capability significantly mediates the relationship between all independent variables and marketing performance, validating the Composition-Based View's (CBV) premise that firms can achieve competitive advantage through strategic resource composition. The findings suggest that SMEs can enhance their marketing performance by developing resilient compositional capability, which enables them to creatively integrate and optimize their resources in response to market challenges.